Mengimplementasi Senam Otak Untuk Meningkatkan Konsentrasi Anak -Anak Dalam Menghadapi Belajar Online Di Era Covid 19 - Selviani, Diah; Juwita; Suryani , Novi Ade; Susanto , Edy; Lubis, Nurhanifah (Jurnal Kewirausahaan dan Bisnis, 2020)
The COVID-19 pandemic has forced many children to adapt to online learning. In this context, the problem that often arises is a lack of concentration and focus on learning material. Therefore, this study aims to analyze the effectiveness of implementing brain exercises as a method that can increase children's concentration in dealing with online learning in the era of COVID-19. Data collection was carried out using a concentration test instrument that has been tested for validity and reliability. Concentration tests were performed before and after the intervention period of several weeks. The collected data were then analyzed using statistical analysis. The results of this study indicate that the intervention group who underwent regular brain exercises experienced a significant increase in their concentration compared to the control group. Brain exercise can improve children's ability to focus attention, reduce distractions, and improve their memory skills. In the context of online learning in the era of COVID-19, the implementation of brain gymnastics can be an effective method for increasing children's concentration. Brain gym is a form of exercise that involves body movement, brain coordination, and sensory stimuli. Structured movements in brain gymnastics can stimulate children's brain development, thereby helping them to better face the challenges of online learning. This study provides recommendations to schools and parents to implement brain exercises as part of children's routines before online learning sessions. Brain gym can be an effective strategy in helping children improve concentration, maintain their attention, and optimize learning outcomes in unfamiliar online learning situations.